BUMN dan Penguasaan Negara di Sektor Pos [SOEs and State Authority in Postal Sector] - Muhammad Insa Ansari (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2017)
This paper discusses the study of SOEs and state control of the postal sector. The study was conducted using normative legal research methods. In this normative legal research used primary legal materials, secondary legal materials, and tertiary legal materials. The results of the study indicate that the state's control of postal activities is changing according to the economic system adopted by the government in power. In the old order of state control of the postal activity is very dominant, even the Postal Service, Telegram and Telephone have the authority to conduct a monopoly. In the new order era of state control of the postal sector began to decrease even during the order of reform of state control of the postal sector only as a regulator only. However, during the reform order period there were a number of state obligations carried by SOEs in the form of public service obligations to organize posts in remote areas.*****Naskah ini membahas kajian terhadap BUMN dan penguasaan negara pada sektor pos. Kajian dilakukan dengan menggunakan metode penelitian hukum normatif. Dalam penelitian hukum normatif ini digunakan bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Hasil kajian menunjukkan bahwa penguasaan negara terhadap kegiatan pos berubah sesuai dengan sistem perekonomian yang dianut oleh pemerintah yang berkuasa. Pada masa orde lama penguasaan negara terhadap kegiatan pos sangat dominan, bahkan Jawatan Pos, Telegram dan Telepon memiliki kewenangan untuk melakukan monopoli. Pada masa orde baru penguasaan negara terhadap sektor pos mulai berkurang bahkan pada masa orde reformasi penguasaan negara terhadap sektor pos hanya sebagai regulator saja. Namun demikian pada masa orde reformasi ada sejumlah kewajiban negara yang diemban oleh BUMN dalam bentuk kewajiban pelayanan umum untuk menyelenggarakan pos di daerah-daerah terpencil.